Developing a Toolkit to Evaluate Listening Comprehension and Speech Use Abilities of Children Aged 12 to 36 Months (Journal of Contemporary Educational Policies and Practices, 2025)
Children’s language development is crucial for play, learning, and communication. It is greatly significant for cognitive development, personality formation, and growth. Children’s language development is particularly thriving between the ages of 12 and 36 months, when they begin to communicate through social interactions in certain settings. The aim of this study is to develop a toolkit to evaluate children’s abilities between the ages of 12 and 36 months in terms of their listening comprehension and speech use skills. Data was drawn from an experimental process of the toolkit conducted on 303 children aged from 12 to 36 months from various regions in Khanh Hoa province, consisting of urban, rural and mountainous areas. The results demonstrate high internal consistency, criterion validity and toolkit reliability. This study has practical implications for pedagogical lecturers and students majoring in Early Childhood Education for teaching, learning and scientific purposes; for preschool teachers in assessing children’s language development, allowing them to choose appropriate content, methods, and educational forms to effectively support the children’s language development as well as for parents in evaluating their children’s language proficiency in order to proactively seek professional assistance if necessary.
Keywords: Assessment tools; language ability; listening comprehension ability; speech use ability; children 12-36 months